Orexin-A exerts neuroprotective effect in experimental intracerebral hemorrhage by suppressing autophagy via OXR1-mediated ERK/mTOR signaling pathway - Zhang, Dexin; Cui, Ying; Zhao, Manman; Zheng, Xuecheng; Li, Chunyan; Wei, Jingbo; Wang, Kaijie; Cui, Jianzhong (Frontiers in Cellular Neuroscience, 2022)
Orexin-A (OXA) is a polypeptide produced in the hypothalamus, which binds to specific receptors and exerts multiple physiological effects. Autophagy plays a vital role in early brain injury (EBI) after intracerebral hemorrhage (ICH). However, the relationship between OXA and autophagy after ICH has not been confirmed. In this study, the protective role of OXA was investigated in a model of hemin-induced injury in PC12 cells and blood-injection ICH model in rats, and its potential molecular mechanism was clarified. Neurobehavioral tests, brain water content, and pathologic morphology were assessed after ICH. Cell survival rate was determined using Cell Counting Kit-8 (CCK-8), while apoptosis was detected using flow cytometry. The autophagy protein LC3 that was originally identified as microtubule-associated protein 1 light 3 was evaluated by immunohistochemistry. The ultrastructural changes of cells following ICH were observed by transmission electron microscopy. Western blotting was performed to determine the expression levels of LC3, p62/SQSTM1 (p62), phosphorylated extracellular signal-regulated kinase 1/2 (p-ERK1/2), total extracellular signal-regulated kinase 1/2 (t-ERK1/2), and phosphorylated mammalian target of rapamycin (p-mTOR). OXA treatment significantly improved neurofunctional outcomes, reduced brain edema, and alleviated neuronal apoptosis. OXA administration upregulated p-mTOR and p62, while it downregulated pERK1/2 and LC3; this effect was reversed by the orexin receptor 1 (OXR1) antagonist SB-334867. This study demonstrates that OXA suppresses autophagy via the OXR1-mediated ERK/mTOR signaling pathway to exert neuroprotective effects, and it might provide a novel therapeutic approach in patients suffering from ICH.